The Addition of Guava Leaves in Feed to the Blood Glucose of Carp reared in Brackish Water and Infected with Aeromonas hydrophila - Irwan Effendi; Windarti Windarti; Heri Masjudi; Muhammad Rizal Razman; Ahmed Al-Harbi; Nisfi Maulidia Nasution; Tomi Syahputra; Ronal Kurniawan (Jurnal Natur Indonesia, 2023)
Guava leaves can be utilized as feed additives and medicine for aquaculture. Limiting factors in aquaculture, including stocking density, and salinity can cause stress in fish, so they are easily infected with disease. This study was conducted to determine the effect of guava on the blood glucose of carp reared in brackish water media. This research was conducted from August to September 2023 at the Marine Biotechnology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The method used in this study is an experimental method using a completely randomized design with 5 (five) treatments and 3 (three) replicates, the treatments are T0 (control), T1 (1.0g), T2 (1.5g), T3 (2 g), and T4 (2.5g). Carp measuring 5.00 ± 1.00 cm with a weight of 4.00 ± 0.50 g were obtained from farmers in the Koto Panjang hydroelectric reservoir, Sumatra, Indonesia. Fish rearing was carried out for 60 days. The results showed that the provision of guava leaves in the feed affected the blood glucose levels of carp. The dose of 1.5 g/100g feed (T2) was the optimal dose in increasing the blood glucose of carp reared in brackish water media and infected with A. hydrophila bacteria